Analisis Perubahan Makna dan Faktor Penyebab Perubahan Makna dalam Kolom Komentar Instagram @najwashihab - Risma Zulifa, Arfiani; Kustriyono, Erwan (South Sulawesi Education Development, 2026)
Language, based on semantics, is a system of signs or symbols used to convey meaning. In semantic studies, language is understood not only as a means of communication but also as a medium for conveying meaning that is influenced by the situation, culture, and knowledge of the user and listener. A sentence has different meanings, depending on the response or response through interaction in the Instagram comment column. This study aims to examine the forms of meaning change and identify the factors that cause meaning change in the Instagram comment column presents unique language dynamics, including shifts in the meaning that occur due to the context of use, language style, and the socio cultural background of the speaker. That analysis was carried out by classifying the data based on the type of meaning change, such as expansion, narrowing, amelioration, pejoration, and associative changes. The results of the study indicate that changes in meaning in comments are influenced by various factors, including situational context, language creativity, the use of figurative language, and the influence of popular culture. These findings indicate that social media is not only a means of expression but also a space for dynamic language evolution. The implications of this research are expected to be used as teaching materials or teaching guides in news text learning material in class XI in high school.